Precision nitrogen and water management in double zero -till wheat: effects on photosynthetic parameters, productivity, nutrient-use efficiency and N2O emission - Pratap, Vijay; Dass, Anchal; Krishnan, P.; Sudhishri, S.; Choudhary, Anil K.; Bhatia, Arti; Jinger, Dinesh; Verma, Sunil K.; Singh, Arjun; San, Aye Aye; Nithinkumar, K.; Sachin, K. S.; et al. (Frontiers in Plant Science, 2025)
ContextConventional tillage (CT), excessive irrigation, and indiscriminate nitrogen (N) use in wheat farming degrade soil and water resources in the Indo-Gangetic Plains (IGP), threatening the sustainability of the rice-wheat cropping system.ObjectivesA two-year study (2019–21) in north-west IGP was conducted to assess the integration of zero-tillage (ZT) with precision water and N management for sustainability, nutrient efficiency, and environmental performance.MethodsThe study tested two crop establishment methods (ZT-wheat and double ZT-wheat) and three irrigation regimes–25%, 50%, and 75% depletion of available soil moisture (DASM), with silicon applied at 75% DASM–alongside three N strategies: 100% recommended N dose (RDN), NutrientExpert® (NE®) + Leaf Color Chart (LCC), and NE® + SPAD-based N management, using a split-plot design.Results and ConclusionDouble ZT-wheat performed better over conventional ZT, showed superior growth (higher dry matter accumulation, leaf area index, and photosynthetic rate), 3.5% greater interception of photosynthetically active radiation (PAR), and 6.7–9.9% increases in grain/straw yields, and resource-use efficiency. Irrigation at 25% DASM increased photosynthetic activity, intercepted 18.3% more PAR, and yielded 9.23% higher grain over 50% DASM, though delaying irrigation to 50% DASM conserved water without significant yield loss. NE® + SPAD-based N management saved 40 kg N ha–1 while enhancing productivity and efficiency, and combining ZT with 75% DASM + silicon and NE® + LCC significantly reduced N2O emissions, thus suggested for implementation in the wheat growing regions.SignificanceThe current study findings promote precision N-water strategies, and double ZT to enhance productivity, resource conservation, and environmental sustainability in the IGP’s wheat systems addressing important sustainable development goals concerning agriculture.